Determinants of Fraud in the Village Government: The Pentagon's Fraud Perspective - Basri, Yesi Mutia; Fadilla, Olga; Azhar, Al (Universitas Syiah Kuala, 2021)
Objective This study aims to examine and analyze the factors that influence fraud from a pentagon fraud perspective in the Village Government of Kampar Kiri District, Riau Province, Indonesia. The variables used in this study are the suitability of compensation which is a proxy for pressure, the effectiveness of the internal control system is a proxy for opportunity, organizational culture is a proxy for rationalization, competence is a proxy for ability and leadership style is a proxy for arrogance.Design/methodology The population in this study were all villages in Kampar Kiri District, Riau Province, Indonesia. Respondents in this study were village apparatuses in the Kampar Kiri district. A total 90 respondents participated in this study spread across 19 villages. Data was collected using a questionnaire sent to respondents. Meanwhile Structural Equation Modeling (SEM) analysis with SmartPLS analysis version 3.2.6 was utilized to analyze the data.Results The results of this study indicate that the suitability of compensation, the effectiveness of the internal control system, organizational culture, competence and leadership style affect the fraud on the village government.Research limitations/Implication This research was only carried out in the village of Kampar Kiri and only five variables were used as a proxy for the fraud pentagon. This research implies that policies need to be further strengthened to reduce the occurrence of fraud in the village government.Novelty/Originality - This research was conducted in a village government environment in the Kampar Kiri sub-district of Riau Province. The crowd of fraud in the village administration has disrupted public services and community welfare. Previous research has focused more on local government hence research at the village government is interesting and pertinent to study.